Depression, stroke and gender: evidence of a stronger association in men. Issue 3 (26th June 2014) - Hamano, Tsuyoshi; Li, Xinjun; Lönn, Sara Larsson; Nabika, Toru; Shiwaku, Kuninori; Sundquist, Jan; Sundquist, Kristina
Abstract : Background/aims: Depression is associated with an increased risk for stroke. The aim of this study was to examine whether demographic and socioeconomic factors modify this association. Methods: This follow-up study comprised 137 305 men and 188 924 women aged ≥30 years from a nationwide sample of primary healthcare centres in Sweden. We identified 4718 first-ever stroke cases (2217 men and 2501 women) during the follow-up period (2005–2007). Multilevel logistic regression models were used to calculate ORs and examine interactions in order to determine whether the association between depression and stroke differs by demographic or socioeconomic factors. Results: Depression was associated with significantly greater odds of stroke after adjustment for potential confounding factors (OR=1.22, 95% CI 1.08 to 1.38). Interaction tests showed that the effect of depression on stroke was higher in men compared with women (the difference in OR between men and women was 1.30, 95% CI 1.01 to 1.68), that is, the association between depression and stroke was modified by gender. Conclusions: Our findings suggest that the depression–stroke association is modified by gender. Further studies are required to examine the underlying mechanisms in men and women.